Pooling Health Risk to Protect People : An Assessment of Health Insurance Coverage in Philippines - World Bank (World Bank, Washington, DC, 2017)
Taking the Philippines Health Financing Strategy (HFS) 2010–2020 objective of ‘sustaining membership in PhilHealth for all Filipinos’ as its point of departure, this report assesses the expansion of health insurance coverage in the Philippines and the extent to which it provides protection from out-of-pocket (OOP) health spending. The report commences with a description of the organization of social health insurance through PhilHealth, the different PhilHealth membership groups, their eligibility criteria, contribution structure, and benefits. Using both administrative data and household surveys, the report then analyzes the patterns and trends in PhilHealth membership over time and discusses the drivers of membership expansion among different membership groups. Because the HFS and the country’s health insurance laws stress the link between the objective of sustaining membership in PhilHealth and the attainment of equity and financial protection goals, the equity dimension of PhilHealth membership gets special attention. In this regard, the report looks at equity in coverage, contributions, benefit design, and benefit payments, as well as performance on financial protection measures. It concludes by proposing some future directions, together with associated specific recommendations.